Human Resource Development Strategy in Improving Teacher Performance and the Quality of Madrasah Tsanawiyah - Anwar, Miftahul; Abun, Ahmad Rifai; Mujiyatun, Mujiyatun (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This study aims to analyze human resource (HR) development strategies in improving teacher performance and the quality of Islamic Junior High Schools (Madrasah Tsanawiyah). The studyis background is the importance of the quality of educational human resources as a major factor in the success of Islamic educational institutions, especially in meeting the demands for learning quality, teacher professionalism, and madrasa competitiveness. The study used a qualitative, multi-site approach across three Madrasah Tsanawiyah in South Lampung Regency: MTs Negeri 4 South Lampung, MTs Mathla'ul Anwar Cintamulya, and MTs Hidayatul Mubtadiin Jati Agung. Data were collected through in-depth interviews, observation, and documentation, then tested for validity through triangulation of sources, techniques, and time. Data analysis was carried out through single-site and cross-site analysis. The results of the study indicate that HR development strategies are implemented through the POAC (Planning, Organizing, Actuating, Controlling) management function which includes teacher needs planning, ongoing training, academic supervision, teacher empowerment, performance evaluation, and strengthening work culture. This strategy impacts teacher competence and performance, learning innovation, work discipline, and the quality of madrasahs as institutions. This study recommends an adaptive, collaborative, and sustainable human resource development model for Madrasah Tsanawiyah.